The Effect of PDEODE Learning Strategy (Predict – Discuss – Explain – Observe – Discuss - Explain) on Students’ Critical Thinking Skills on Sound Wave Material - Amelia Putri Wardhani; Fathiah Alatas (Kasuari: Physics Education Journal (KPEJ), 2026)
This study was conducted to evaluate the effectiveness of the PDEODE learning strategy in improving students' critical thinking skills on the topic of sound waves. The research method used a quasi-experimental design with a nonequivalent control group design, conducted at a public senior high school in South Tangerang. The research subjects involved two 11th-grade science classes, with one class as the experimental group implementing the PDEODE strategy and the other as the control group using a scientific approach. Data were collected through essay tests and then analyzed statistically, complemented by N-Gain and effect size calculations. The research findings revealed that the average post-test score for critical thinking skills in the experimental class (87.81) was significantly higher than that of the control class (54.66), with a significance level of 0.000. The N-Gain calculation for the experimental group was categorized as high (0.83), while the control group was in the medium category (0.42). The effect size calculated using Cohen's d indicated a medium effect category (0.5). Based on these findings, the PDEODE strategy can be considered an innovative learning alternative in the subject of physics.